Recent Advances on Graphene Quantum Dots for Bioimaging Applications - Younis, Muhammad Rizwan; He, Gang; Lin, Jing; Huang, Peng (Frontiers in Chemistry, 2020)
Being a 0-dimensional nanomaterial of carbon family, graphene quantum dots (GQDs) showed promising biomedical applications owing to their ultra-small size, non-toxicity, biocompatibility, excellent photo stability, tunable fluorescence, and water solubility etc., thus captured a considerable attention in biomedical field. This review summarizes the recent advances made in the research field of GQDs and place special emphasis on their bioimaging applications. We briefly introduce the synthesis strategies of GQDs, including top-down and bottom-up strategies. The bioimaging applications of GQDs are also discussed in detail, including optical (fluorescence, FL), two-photon FL, magnetic resonance imaging (MRI), and dual-modal imaging. In the end, the challenges and future prospects to advance the clinical bioimaging applications of GQDs have also been addressed.